TMS-evoked potential in the dorsolateral prefrontal cortex to assess the severity of depression disease: a TMS-EEG study - Li, Xingxing; Chen, Meng; Liu, Qinqin; Zheng, Chao; Yu, Chang; Hou, Guangwei; Chen, Zan; Chen, Yiqing; Chen, Yinping; Zhu, Guidong; Zhou, Dongsheng; Xu, Weiqian (Frontiers in Pharmacology, 2023)
Objective: The combined use of transcranial magnetic stimulation and electroencephalography (TMS-EEG), as a powerful technique that can non-invasively probe the state of the brain, can be used as a method to study neurophysiological markers in the field of psychiatric disorders and discover potential diagnostic predictors. This study used TMS-evoked potentials (TEPs) to study the cortical activity of patients with depression (MDD) and the correlation with clinical symptoms to provide an electrophysiological basis for the clinical diagnosis. Methods: A total of 41 patients and 42 healthy controls were recruited to study. Using TMS-EEG techniques to measure the left dorsolateral prefrontal cortex (DLPFC) 's TEP index and evaluate the clinical symptoms of MDD patients using the Hamilton Depression Scale-24 (HAMD-24). Results: MDD subjects performing TMS-EEG on the DLPFC showed lower cortical excitability P60 index levels than healthy controls. Further analysis revealed that the degree of P60 excitability within the DLPFC of MDD patients was significantly negatively correlated with the severity of depression. Conclusions: The low levels of P60 exhibited in DLPFC reflect low excitability in MDD; the P60 component can be used as a biomarker for MDD in clinical assessment tools.